A Política de Direitos dos Refugiados e a Democratização de Acesso à Rede Pública de Ensino em Manaus: Refugee Rights Policy and Democratization of Access to Manaus Public Education Network (Revista Cocar, 2021)
Palavras-chave: Refúgio; Política; Educação.  AbstractThis qualitative study with bibliographic analysis aims to explore the concepts of refugees, the international and national policy on refuge and the access of students in refugee situations to education in the city of Manaus. Therefore, the public school system had to adapt and face the challenge of absorbing children who moved with their parents to a different cultural, social and linguistic reality. Therefore, the results are embodied in the analysis of the interpreted cataloging of policies and legal guarantees that project possibilities and ways for education to be plural and diversified. It also presents the descriptive and formative compilation of the legal and administrative processes of action by the State as an education provider for students in refugee situations in Manaus.Key words: Refuge; Politics; Education.